The Use of Artificial Intelligence Technologies in Public Relations Practices within Saudi Organizations A Survey Study on a Sample of Public Relations Practitioners in the Kingdom of Saudi Arabia - Alkahtani, Abdulhadi Mohammed Almfleah (Journal of Posthumanism, 2025)
The study aimed to identify the extent to which artificial intelligence (AI) technologies are used in public relations practices in the Kingdom of Saudi Arabia. The research adopted quantitative methodologie to examine the use of AI technologies in public relations within the Kingdom. The study was conducted among all public relations practitioners, including experts in Saudi institutions, using a quantitative approach. A questionnaire was distributed to 53 practitioners, with a sample of 53 respondents. The study yielded several key findings, most notably that the application of AI in public relations across Saudi organizations varies. AI is used more extensively in content creation and data analysis, while its adoption remains limited in some institutions. The majority of practitioners do not view AI as a replacement for human involvement but rather as a supportive tool to enhance efficiency and performance.